Latin American Neostructuralism: The Contradictions of Post-Neoliberal Development - Sheinin, David (Labour / Le Travail, 2009)
The article reviews the book, "Latin American Neostructuralism: The Contradictions of Post-Neoliberal Development," by Fernando Ignacio Leiva.
Keywords: BOOKS – Reviews; LATIN American Neostructuralism: The Contradictions of Post-Neoliberal Development (Book); LEIVA; Fernando Ignacio; Neoliberalism; Nonfiction